Some Elements in The Fruit: An Assessment of Gingerbread Plum from Sokoto, Nigeria - Aminu Umar Imam; Sambo Umar Shehu; Yusuf Sarkingobir; Yusuf Yahaya Miya; Shafiu Ismaila Adili; Abubakar Shehu; Abdullahi Alhaji Adamu (Journal of Bioresources and Environmental Sciences, 2023)
A region like Sokoto that is been challenged by series of problems such as double burden of diseases, malnutrition, and food insecurity should utilized the available fruits for their inherent nutrient’s compositions. Therefore, the objective of this study was to assess the proximate and elemental contents (sodium, phosphorus, potassium, calcium, and magnesium) in gingerbread plum (Neocarya macrophylla) fruit which are essential for normal growth and development of body tissues for the human health. Neocarya macrophylla fruit is screened for certain nutritionally needed elements and proximate compositions using standard methods. Results obtained show that, crude protein with (2.70 ± 0.0057%) has the lowest concentration, the moisture content was 5.83 ± 0.57 percent, ash content was 5.33 ± 1.54 percent, crude lipid was 5.23 ± 0.15 percent, and crude fiber was 13.33 ± 4.48 percent. The determined levels of mineral elements (calcium, magnesium, phosphorus, sodium, and potassium) reveal 30.25000 ppm, 4.9001 ppm, 90. 1000 ppm, 40.563 ppm, and 67.5601 ppm, respectively. Therefore, the plant is nutritious and vital for metabolic processes.